How to Construct Super Edge-Magic Total Labeling of Theta Graph θ(2,b,c) - Mujtahid, Zainul; AN, M Salman; Hidayat, Amam Taufiq; Qausar, Haves; Zahara, Yulia (Indonesian Journal of Mathematics Education, 2024)
This research study and provide the property of super edge-magic total labelings of theta graph. Edge magic labeling on a graph  is an injective function   from  to a subset of integers { } with the property that there is a positive integer  such as  for each . An edge-magic labeling  is called super edge-magic total labeling if it satisfies . A graph is called (super) edge-magic total if it admits some (super) edge-magic total labeling. A theta graph  is constructed by embedding the endpoints of three paths of length consecutive  such that there are two vertices of degree three and the other of degree two. This study gave some conditions for such a super edge-magic total of theta graph. Based on this condition, this paper introduce some algorithms to apply and develop super edge-magic total labeling from some previous theta graphs.